Study on Effectivity and Efficiency of Various Drying Methods of Nyamplung Fruits (Callophyllum inophyllum). Issue 1 (1st June 2022) - Amelia, Okta; Sailah, Illah; Kartika, Ika Amalia; Suparno, Ono; Bindar, Yazid
Abstract: Nyamplung fruit has a very high industrial potential, especially for the bioenergy industry. The seeds contain high levels of oil that can be transformed into biodiesel. The advantage of nyamplung fruit as bioenergy raw material is that the seeds have a high yield can reach 74%. One of the difficulties of transforming the fruit into a product with high economic potential is in terms of taking out the seed from its shell, which is influenced by the moisture content of the fruit. To reduce the moisture content, nyamplung fruits require a drying process. The drying process is usually done by utilizing sunlight. This method has the disadvantage of taking a long time and is affected by the weather. Therefore, it is necessary to conduct a study to select one of several drying methods based on their efficiency and effectiveness. The study results showed that drying using the oven for 6 hours produced a moisture content of 10% wet base while drying using a 6-hour roasting method produced a moisture content of 6.5% wet base, and drying using sunlight for 168 hours produced a moisture content of 10.23% wet base. Water content between 6.5-10.23% makes separating seeds from their shells easy. Based on this study, it can be concluded that drying methods affect the moisture content of the fruit, and the method of drying using the oven turned out to be more effective.